2021
DOI: 10.1093/infdis/jiab603
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length Declines in Persons With Human Immunodeficiency Virus Before Antiretroviral Therapy Start but Not After Viral Suppression: A Longitudinal Study Over >17 Years

Abstract: Background In people living with HIV (PWH), long-term telomere length (TL) change without/with suppressive antiretroviral therapy (ART) and the contribution of genetic background to TL are incompletely understood. Methods We measured TL change in peripheral blood mononuclear cells by quantitative PCR in 107 Swiss HIV Cohort Study participants with longitudinal samples available both before and during suppressive ART. We appli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…While cART treatment has been shown to reduce molecular markers of aging from that seen in chronically infected, untreated individuals in peripheral tissues [3][4][5], to our knowledge the impact of cART on biological aging in the brain has not previously been reported. Here, we found that p16 levels in cART treated animals only differed from that seen in chronically SIV-infected, untreated animals in a couple brain regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cART treatment has been shown to reduce molecular markers of aging from that seen in chronically infected, untreated individuals in peripheral tissues [3][4][5], to our knowledge the impact of cART on biological aging in the brain has not previously been reported. Here, we found that p16 levels in cART treated animals only differed from that seen in chronically SIV-infected, untreated animals in a couple brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of the cellular senescence marker p16 INK4a (p16) in T cells correlated with chronological age in uninfected controls and HIV-infected, cART-treated individuals, but was signi cantly higher in HIV-infected untreated individuals, indicating an accelerated aging phenotype [3,4]. Additionally, in a recent longitudinal study of PLWH, epigenetic aging in peripheral blood mononuclear cells was also found to accelerate with HIV infection and decelerate after successful viral suppression with cART [5], demonstrating an accelerated aging phenotype with HIV infection that is inhibited by cART. However, when looking at what is occurring within the CNS, support for accelerated biological aging is more limited, especially in the context of cART.…”
Section: Introductionmentioning
confidence: 99%
“…Although older studies indicated a negative effect of cART on telomere length [ 24 , 51 , 54 ], several recent studies presented different results. Recent findings have shown that initiating suppressive cART has a positive effect on telomeres and reverses their decrease in length [ 24 , 55 , 56 ]. Not only that telomere length increases during suppressive cART, but also that T cells increase their replicative potential while telomeres become longer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methylation patterns are also used to generate epigenetic clocks to assess biological age and deviations from chronological age. Advanced methylation aging is apparent in ART-naive PLWH [46,47 ▪▪ ] and can begin during the earliest stages of acute infection [48 ▪▪ ,49]. Post-ART longitudinal studies show deceleration in epigenetic age with viral suppression, stressing the importance of early diagnosis and limiting the delay in ART initiation.…”
Section: Biological Aging Hallmarksmentioning
confidence: 99%